RNA methodologies a laboratory guide for isolation and characterization - Farrell, Robert E. Jr (Academic Press, 2022)
"RNA Methodologies: A Laboratory Guide for Isolation and Characterization, Sixth Edition provides the most up-to-date ribonucleic acid lab techniques for seasoned scientists and graduate students alike. This edition features new material on RNA sequencing, RNA in Situ Hybridization, non-coding RNAs, computational RNA biology, transcriptomes and bioinformatics, along with the latest advances in methods and protocols across the field of RNA investigation. As a leader in the field, Dr. Farrell provides a wealth of knowledge on the topic of RNA biology while also giving readers helpful hints and troubleshooting techniques from his own personal experience in this subject area. This book presents the essential knowledge and techniques to use when working with RNA for the experienced practitioner, while also aiding the beginner in fully understanding this important branch of molecular biology."